BIMBINGAN KELOMPOK BERBASIS PENDEKATAN HUMANISTIK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA (Universitas Negeri Semarang, 2014)
abstrakPenelitian ini dilakukan berdasarkan temuan empirik yang menunjukkan bahwa motivasi belajar pada siswa kelas XI SMA Negeri 8 Pontianak tahun pelajaran 2012/2013 tergolong rendah untuk aspek-aspek tertentu, untuk itu perlu diberikan tindakan dari model yang telah dirancang. Penelitian ini menghasilkan model bimbingan kelompok berbasis pendekatan humanistik untuk meningkatkan motivasi belajar siswa. Dari uji efektifitasyang dilakukan bahwa model bimbingan kelompok berbasis pendekatan humanistik efektif untuk meningkatkan motivasi belajar siswa. Hipotesis menunjukkan bahwa semua indikator motivasi belajar siswa mengalami peningkatan yangberarti setelah diberikan bimbingan kelompok berbasis pendekatan humanistik.abstractMotivation learning student is a classsic problem, if left unchecked willbe bad forthe successand achieve-ment. Lowstudent motivationis a formofbehaviorthat don’t haveself-awarenessandsense ofresponsibilityas student.Success oflearningis strongly influencedby themotivation learning.Researchproblemishow to model group guidance based on humanistictoincreaselearning motivation student. Purpose this research is made a model group guidance based on humanistic to increase motivation learning student.Research use methodresearchand developmentwith stepsasfollows:1) Phasepreliminary study,2) planning,3) hypotheti-cal model, 4) review of model, 5) testfield, 6) finaltest. Sampleselected bypurposive sampling. Modelgroup guidance based on humanisticthatdevelopedprocess ofassistance providedbycounselorsto studentsthrough-group dynamicstoimprovelearning motivationto eachmember ofthe throughthe utilization experienceof groupmembers. Results showedthatthere’san increase initialevaluation ofthe final evaluationscore of164.9points. This indicatesthat the modeldevelopedproven effective in improvingstudent motivation. Suggestion: model groups guidance based on humanisticcan beusedasa solutionto solvethe problems mo-tivation learning.